Dynamic Water Scheduling in the Northwest River Delta Basin Based on Minimum Discharge Flow Control in Cross-section - WU Di; FANG Chunyan; SHANG Yunfei (Renmin Zhujiang)
In response to the problem of insufficient future demand forecasting and poor scheduling balance caused by traditional watershed water scheduling methods relying on historical data and fixed rules, a dynamic water scheduling method for the Northwest River Delta Basin based on minimum discharge flow control of cross-sections was proposed. By using the grey prediction model, the production and domestic water consumption in the downstream areas of the Northwest River Delta Basin was accurately predicted. The Tennant method was used to calculate ecological base flow and evaluate specific ecological water requirements such as wetlands, so as to ensure the healthy and sustainable development of the ecosystem in the basin. On this basis, by taking into account both ecological water demand and socio-economic water demand, the minimum discharge flow control index of the cross-section was determined, and a fitness function was constructed. The whale optimization algorithm was used to find the optimal water allocation plan. The experimental results show that the method proposed in this paper can effectively identify excess water that exceeds the current demand or storage limit and achieve balanced water allocation. In the dry season scheduling of 2023, the measured minimum flow rate is 228 m3/s, with a satisfaction rate of 106%, significantly improving scheduling efficiency and effectiveness and laying a solid foundation for the sustainable development of water resources management in the basin.